Concurrent hardware architecture for dual-mode audio steganography processor-based FPGA - Shahadi H.I.; Jidin R.; Way W.H. (Elsevier Ltd, 2023)
Computer architecture; Field programmable gate arrays (FPGA); Hardware; Parallel processing systems; Programmable logic controllers; Signal to noise ratio; Steganography; Wavelet transforms; Audio steganography; Dual modes; Field programmable logic; Lifting wavelet transforms; Security; Computer hardware description languages